Pengaruh Solvabilitas, Profitabilitas, Likuiditas, dan Biaya Operasional terhadap Book Tax Differences: Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024 - Badrus Agusandara; Tresno Eka Jaya; Hera Khairunnisa (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2026)
This study examines how solvency, profitability, liquidity, and operating costs are affected by book-tax differences (BTD) among property and real estate companies listed on the Indonesia Stock Exchange from 2022 to 2024. One key indicator of financial reporting transparency is BTD, which reflects the difference between accounting and taxable income. This is particularly relevant for the property sector, which contributes Rp185 trillion to national tax revenue. The results of the study, conducted using the Random Effects Model panel data regression method with 93 observations from 31 companies, show that solvency (DER) has a significant effect on BTD, while profitability (ROA) also has a significant effect, indicating that companies with high profits tend to engage in more aggressive tax planning practices and financial reporting strategies. On the other hand, liquidity and operating costs do not have a significant impact on corporate tax reporting behavior. 98% of the variation in BTD can be explained by the model.